Janusz Mariański, Human Dignity – Appreciated Virtue or Empty Phrase? Sociopedagogical Study, Publishing House: Warszawskie Wydawnictwo Socjologiczne, Warsaw 2019, pp. 338 - Zduniak, Agnieszka (Uniwersyteckie Czasopismo Socjologiczne, 2019)
Modern society has to deal with multiple social, environmental and bioethical problems. In general there attempt to resolve these problems using scientific and technological means based on the rationality criteria, regulations and legal sanctions. This is the way of subjecting social life to the market forces and the interests of giant organisations. It is becoming less favourable for those who are for the various reason unable to demonstrate individual achievements, social relevance and other characteristics that provide sufficiently high social status and enable people to make full use of freedom and opportunities that are available in the fast changing world. In the perspective of the political and economic systems a human being is not a unique, one person of a kind any more. It is an element of the social structure that can be replaced when needed, exchanged for another one with the similar characteristics. Therefore it is more often pointed out that social order should be based on the ethical norms. They represent more reliable guarantee of the harmonious performance than purely organisational regulations. It involves the necessity to restore the former meaning of the concept of human dignity. There is more frequent recognition of the need to base the most important legal regulations on normative foundations and the fact that without reference to the concept of human dignity it is impossible to properly understand human rights.